Pendidikan Literasi Ekonomi: Penguatan Sikap Cinta, Bangga, dan Paham Rupiah Pada Siswa SD Kristen Uraur, Seram Bagian Barat - Johan B. Bension; Petrosina Rupisiay; Linda Hatulely; Petrecia Papuani Lamen; Gabriel Adam Taberima; Dhea Mayoletta P. Lesnussa (Jurnal Informasi Pengabdian Masyarakat, 2026)
The “Love, Pride, and Understanding the Rupiah” outreach event held at Uraur Christian Elementary School in Kairatu Subdistrict, West Seram Regency, was successfully implemented and received positive responses from students and school officials. The activity aimed to increase students’ understanding of the Rupiah as Indonesia’s official currency and as a symbol of national sovereignty and pride. The materials covered the concepts of loving the Rupiah, taking pride in using it, understanding responsible financial behavior, and recognizing the characteristics of genuine Rupiah currency. Interactive methods, including presentations, discussions, question-and-answer sessions, and educational games, were used to encourage active participation and facilitate learning. The students’ enthusiasm throughout the activity showed that financial literacy education can be effectively introduced at the elementary school level. The results indicated an improvement in students’ understanding of how to care for and maintain Rupiah currency, the importance of saving, spending money wisely, and identifying genuine banknotes through the 3D method—looking, feeling, and holding the currency up to the light. In addition, the activity helped foster patriotism, responsibility, and awareness of the importance of valuing the national currency from an early age. It is expected that students will apply the knowledge gained in their daily lives and continue to appreciate the Rupiah as a symbol of Indonesian national pride.